The effectiveness of the oral storytelling strategy in improving imagination skills among third-grade intermediate students in the subject of the Holy Quran and Islamic education in Al-Anbar Governorate - Dr.Zuhair Ahmed Abdullah (Journal of College of Education, 2025)
The study sample included (58) students selected by the intentional method, and they were divided into two experimental groups consisting of (30) students studied using the oral storytelling strategy and a control group consisting of (28) students studied in the usual way, the study tool was an essay test to measure imagination skills consisting of (11) paragraphs, After the researcher had done the tribal and dimensional application of the study tool, the results revealed that there were significant differences at the level of (0.05=α) between the experimental and control groups in favour of the oral storytelling strategy and there were significant differences between the average students of the experimental group and the control group on imagination skills in favour of the experimental group .
Keywords: oral storytelling, improving imagination skills, Third Intermediate